Properties of the System for the Mixed Function Oxidation of Kaurene and Kaurene Derivatives in Microsomes of the Immature Seed of Marah macrocarpus: Cofactor Requirements - Hasson, Edna P. (1976)
The rates of oxidation of ent-kaur-16-ene to ent-kaur-16-en-19-ol, ent-kaur-16-en-19-al, ent-kaur-16-en-19-oic acid, and ent-kaur-16-en-7α-ol-19-oic acid are maximal in microsomes prepared from the endosperm of immature Marah macrocarpus seeds in which the cotyledons are approximately one-half the overall length of the seed. The supernatant fraction remaining from the preparation of the microsomes contains factors which stimulate the rates of oxidation catalyzed by the microsomes. Added TPNH is more effective than added DPNH in meeting the requirement for reduced pyridine nucleotide. A mixture of DPNH, ATP, and TPN(+) is much more effective than DPNH alone. Experiments with 2,4-dinitrophenol as a selective inhibitor indicate that the ATP-stimulated synthesis of TPNH which occurs in these microsomes in the presence of this mixture of coenzymes provide TPNH for use in the mixed function oxidations. Relatively low concentrations of DPNH and TPNH together are much more effective than either alone at equivalent concentration. This is consistent with the involvement of two pathways of electron transfer associated with the mixed function oxidations, one of which preferentially utilizes TPNH and the other favoring DPNH. FAD added to microsomes at an optimal concentration of about 10 μm in the presence of TPNH stimulates the rate of the oxidations; higher concentrations are inhibitory. FMN by itself does not produce this stimulation. However, FMN and FAD added together at low concentrations (0.5 μm each) have approximately the same effectiveness as FAD alone at 10 μm. This suggests a role for both flavin nucleotides in the normal electron transfer pathways associated with these oxidations. Some of the stimulatory properties of the supernatant fraction may be accounted for by its content of reduced pyridine nucleotides, FAD, and FMN; the concentrations of FAD and FMN were determined to be 1.1 μm and 0.4 μm, respectively. However, the effects of the supernatant fraction are not completely explained by its content of these coenzymes since other experiments indicate the presence of a heat-labile, nondialyzable stimulatory factor(s) in the supernatant fraction in addition to heat-stable, dialyzable fractors.